2020
DOI: 10.3897/mycokeys.73.53028
|View full text |Cite
|
Sign up to set email alerts
|

Caliciopsis moriondi, a new species for a fungus long confused with the pine pathogen C. pinea

Abstract: The genus Caliciopsis (Eurotiomycetes, Coryneliales) includes saprobic and plant pathogenic species. Caliciopsis canker is caused by Caliciopsis pinea Peck, a species first reported in the 19th century in North America. In recent years, increasing numbers of outbreaks of Caliciopsis canker have been reported on different Pinus spp. in the eastern USA. In Europe, the disease has only occasionally been reported causing cankers, mostly on Pinus radiata in stressed plantations. The aim of this study was to clarify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…calicioides ), ascospores ellipsoidal to subglobose or ovoid (except C . indica ) with smooth walls (Fitzpatrick, 1942b; Garrido‐Benavent & Pérez‐Ortega, 2015; Migliorini et al, 2020; Pratibha et al, 2010). Because the genus Hypsotheca has only recently been resurrected and one of its species, Hypsotheca eucalyptorum , was described only from culture, the description of morphological characteristics for this genus is limited, especially regarding the sexual morph.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…calicioides ), ascospores ellipsoidal to subglobose or ovoid (except C . indica ) with smooth walls (Fitzpatrick, 1942b; Garrido‐Benavent & Pérez‐Ortega, 2015; Migliorini et al, 2020; Pratibha et al, 2010). Because the genus Hypsotheca has only recently been resurrected and one of its species, Hypsotheca eucalyptorum , was described only from culture, the description of morphological characteristics for this genus is limited, especially regarding the sexual morph.…”
Section: Discussionmentioning
confidence: 99%
“…Those authors showed that species of Caliciopsis that had not had their identity confirmed by DNA sequence data might not actually belong to the genus, and thus, their morphology may not be representative of the genus. If only the nine species confirmed as Caliciopsis by sequence data are taken into account (Table 3), the common morphological traits are ascomata over 1 mm tall (except for C. indica and C. moriondi), with the ascigerous swelling terminal to subterminal (except C. calicioides), ascospores ellipsoidal to subglobose or ovoid (except C. indica) with smooth walls (Fitzpatrick, 1942b;Garrido-Benavent & Pérez-Ortega, 2015;Migliorini et al, 2020;Pratibha et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amplifications were carried out in a Mastercycler (Eppendorf, Hamburg, Germany) using the following PCR conditions: initial denaturation at 95 °C for 5 min; followed by 35 cycles of denaturation at 94 °C for 90 s, annealing at 56 °C for 1 min, and extension at 72 °C for 2 min; and a final elongation step at 72 °C for 10 min. (Migliorini et al 2020). Amplification products were separated by electrophoresis on gels containing 1% (w/v) of agarose LE (GeneSpin).…”
Section: Isolate Sequencing and Taxonomical Analysismentioning
confidence: 99%